eHealth Literacy Training Among Carers of Older People and People with Dementia: A Modified Delphi Survey - Efthymiou, Areti; Menikou, Ioanna; Stylianides, Antonis; Geronikola, Nikoletta; Ilieva, Irina; Kancheva, Ivana; Tagliani, Manuela; Seneca, Rita; Mintus, Beata; Sakka, Paraskevi; Papastavrou, Evridiki (My University, 2020)
New web-based services emerge to support carers in their role, but little is known regarding the way that carers use the internet or any related services. In an effort, to improve the health-related digital skills of carers aiming to support their caring role, we have developed eHealth Literacy Learning Skills among Carers of People with Dementia, the eLILY project. This paper presents the findings of a modified Delphi survey planned and delivered in the framework of the project as an effort to integrate stakeholders' knowledge and expertise in the proposed curriculum.
Keywords: Aging; Caregivers; Dementia; eHealth; Literacy